2021
DOI: 10.1101/2021.03.13.435256
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for backtracking by the SARS-CoV-2 replication-transcription complex

Abstract: Backtracking, the reverse motion of the transcriptase enzyme on the nucleic acid template, is a universal regulatory feature of transcription in cellular organisms but its role in viruses is not established. Here we present evidence that backtracking extends into the viral realm, where backtracking by the SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) may aid viral transcription and replication. Structures of SARS-CoV-2 RdRp bound to the essential nsp13 helicase and RNA suggested the helicase facilitates backt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 77 publications
4
67
0
Order By: Relevance
“…Our dimer structure suggests a model for sgRNA synthesis that extends a recent proposal 31,32 ( Figure 2 ). In the model, one RdRp of the dimer (RdRp 1) synthesizes sgRNA from the 3’ end of the gRNA template until it reaches a TRS in the template body (TRS-B).…”
Section: Figuresupporting
confidence: 87%
See 1 more Smart Citation
“…Our dimer structure suggests a model for sgRNA synthesis that extends a recent proposal 31,32 ( Figure 2 ). In the model, one RdRp of the dimer (RdRp 1) synthesizes sgRNA from the 3’ end of the gRNA template until it reaches a TRS in the template body (TRS-B).…”
Section: Figuresupporting
confidence: 87%
“…Due to the lack of one nsp8 subunit, the dimeric RdRp is predicted to have lower processivity than monomeric RdRp 10,14 and this may facilitate TRS recognition. The viral helicase nsp13 could then cause backtracking of the RdRp 31,32 . Backtracking exposes the 3’-end of the nascent sgRNA, which is complementary to the TRS and may hybridize with another TRS located in the leader (TRS-L) at the 5’-end of the template.…”
Section: Figurementioning
confidence: 99%
“…The impact of M501 on SARS-CoV-2 mutation rate can be explained by our proposed model. Moreover, another recent study reported a SARS-CoV-2 RdRp structure with nucleotide analogs and finds the mis-incorporated nucleotide analogs can pause the RdRp function, allowing nsp13 to induce backtracking, which forces the 3 0 end of the primer RNA out the NTP-entry channel (Malone et al, 2021). The direction of the primer RNA 3 0 end out the NTP-entry channel is consistent to that observed in the dCap(0)-RTC structure, this being toward the catalytic center of nsp14 ExoN.…”
Section: Discussionmentioning
confidence: 99%
“…However, like remdesivir, molnupiravir escapes viral RNA proofreading because M incorporation and Mdirected misincorporation are apparently not recognized by the viral exonuclease 23,24 . Such proofreading escape may also be due to the stability of the M-G and M-A base pairs that are predicted not to induce or favor backtracking of RdRp, which is likely required for exposing the RNA 3'-end to the proofreading exonuclease 49,50 . Finally, the two-step model can explain how molnupiravir or NHC monophosphate leads to RNA mutagenesis by polymerases of other viruses.…”
Section: Discussionmentioning
confidence: 99%